Control biológico del Oídium sp mediante el uso de fungicidas biocontroladores en el cultivo del rosal (Rosa sp), en la zona de Cayambe, provincia de Pichincha - Robalino, Wilmer Cristian (2015)
This research was aimed at biological control of the fungus Oidium sp using biocontrol fungicides rose growing in the flower greenhouses Rosadex company Cia. Ltda, located in the Santa Clara, Canton Cayambe, Pichincha province This work was performed in order to assess the crop yield rose (Rosa sp) Tara range, compared to the different applications of biocontrol agents; identify which of the products and the doses of biocontrol shows the best control of the pathogen and economically analyze the treatments. Seven treatments by combining three biocontrol (Trichoderma harzianum, Bacillus subtilis and lactic acids), two doses (3 and 6 ml / L) and a control without application was investigated. The design of randomized complete block (RCBD) was used in factorial arrangement A x B + 1 with 7 treatments and three repetitions, totaling 21 experimental units.......